Boride layer growth kinetics during boriding of molybdenum by the Spark Plasma Sintering (SPS) technology - Yu, L. G. (2012)
Molybdenum borides have potential industrial applications as abrasive, corrosion-resistant and electrode materials due to their high hardness values, chemical inertness, and electronic conductivity. In this work, boride layers are formed on the surface of Mo samples using a pack boriding method with the assistant of the spark plasma sintering (SPS) technique. The process was performed in the temperature range 1000–1400 °C and with a holding time of 30 min at the preset temperature. The microstructure, microhardness, and fracture toughness of the molybdenum boride layer are investigated by optical microscopy, X-ray diffraction and microhardness indentations. Results showed that the boride layer, mainly composed of MoB, have thickness in the range ∼ 6–155 μm. The boriding kinetics is studied by linking the boride layer thickness with the boriding temperature. The activation energy and pre-exponential constant are estimated from the experimental results, and are found to be 218.8 J/mol and 1.41 cm2/s respectively. The MoB layers have a preferred orientation in the (002) direction, which is reflected by a distinct columnar growth observed in the optical micrographs of polished cross-sections of SPS samples.